2019
DOI: 10.1007/s10811-019-01806-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of C-phycocyanin productivity by Arthrospira platensis when growing on palm oil mill effluent in a two-stage semi-continuous cultivation mode

Abstract: Palm oil mill effluent (POME) is well known as agricultural wastewater that has a high potential as a medium for microalgal growth due to its high macro-and micronutrient content. The cyanobacterium Arthrospira platensis is considered as a species with a high C-phycocyanin (C-PC) content which is important for fine chemical and pharmaceutical applications. However, cultivation of A. platensis on POME to produce economically feasible amounts of C-PC has not been well explored. For this, environmental, nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
1
5
1
1
Order By: Relevance
“…The productivity of phycocyanin from S. maxima in various dilutions of ADDMW ranged from 1.04 to 1.39 mg L -1 day -1 . The result from this study is still in the range of Nur et al [21] reported data. The purity of phycocyanin was shown in the purity index, a ratio between the absorbance of phycocyanin at the maximum wavelength (620 nm) and the absorbance of phycocyanin at 280 nm (protein) [22].…”
Section: S Maxima Growth In Addmwcontrasting
confidence: 41%
“…The productivity of phycocyanin from S. maxima in various dilutions of ADDMW ranged from 1.04 to 1.39 mg L -1 day -1 . The result from this study is still in the range of Nur et al [21] reported data. The purity of phycocyanin was shown in the purity index, a ratio between the absorbance of phycocyanin at the maximum wavelength (620 nm) and the absorbance of phycocyanin at 280 nm (protein) [22].…”
Section: S Maxima Growth In Addmwcontrasting
confidence: 41%
“…The initial pH was adjusted to 9.0 ± 0.2 by using 2 N HCl or 2 N NaOH. Salinity was adjusted to 20 PSU as optimum level by using NaCl based on previous results (Nur et al 2019a). External urea (800 mg L −1 ) was added to the medium to avoid nitrogen limitation based on previous experiments (Nur et al 2019a).…”
Section: Effect Of Light and Initial Phenolic Compoundsmentioning
confidence: 99%
“…Salinity was adjusted to 20 PSU as optimum level by using NaCl based on previous results (Nur et al 2019a). External urea (800 mg L −1 ) was added to the medium to avoid nitrogen limitation based on previous experiments (Nur et al 2019a). Every day, the optical density of the culture was measured at 750 nm to determine the growth rate.…”
Section: Effect Of Light and Initial Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations